Scientific mentoring in the educational practice of a student of a pedagogical university - Lyubov A. Kochemasova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Based on the analysis of scientific research, the paper shows the essence of mentoring as a pedagogical phenomenon, examines the meaning and content of scientific mentoring, its role in the educational practice of a student of a pedagogical university.